Analysis of the Factors Influencing the Interest in Using E-Wallets Among Baby Boomers in Koto Lanang Village - Alfianti, Sisfa; Mayasari, Mike (The Future of Education Journal, 2025)
The use of e-wallets among in Koto Lanang Village, with a population of 1,173, shows that younger generations (aged 5-39) are more adept at using new technologies. In contrast, older generations, particularly baby boomers (aged 60-78), tend to be less interested in technological innovations, including e-wallets. This study aims to examine whether ease of use, benefits, and security influence the intention to use e-wallets among baby boomers in Koto Lanang Village. This research uses a quantitative approach with an associative research type. The study population consists of 203 individuals, with a sample size of 50 respondents. Data were collected through questionnaires and interviews and analyzed using validity and reliability tests, as well as classical assumption tests. Data analysis techniques include descriptive analysis and multiple linear regression, along with hypothesis testing (t-test and F-test). The analysis results are expected to show the extent to which the three independent variables, both partially and simultaneously, affect the intention to use e-wallets among the baby boomer generation in Koto Lanang Village. The results of this study indicate that ease of use, benefits, and security have a positive and significant impact on the intention to use e-wallets among the residents of Koto Lanang Village. Partial testing (t-test) shows that all three independent variables have a t-value greater than the t-table and a significance level of < 0.05, namely ease of use (t = 2.478; sig = 0.017), benefits (t = 2.777; sig = 0.008), and security (t = 2.157; sig = 0.036). Simultaneously, the F-test results show an F-value of 21.138 > F-table 2.80 with a significance of 0.000, meaning that the three variables collectively have a significant influence on the intention. The coefficient of determination (R²) value of 0.580 indicates that 58% of the variation in the intention to use e-wallets can be explained by the three variables. These findings emphasize the importance of ease of use, practical benefits, and transaction security as key factors in promoting e-wallet adoption in Koto Lanang Village.